Clinical Risk Factors for the Presence and Development of Vertebral Fractures in Patients With Ankylosing Spondylitis. Issue 5 (May 2017) - Maas, Fiona; Spoorenberg, Anneke; van der Slik, Boukje P. G.; van der Veer, Eveline; Brouwer, Elisabeth; Bootsma, Hendrika; Bos, Reinhard; Wink, Freke R.; Arends, Suzanne
Abstract : Introduction: To investigate the prevalence and incidence of radiographic vertebral fractures and the association with patient characteristics, clinical assessments, and medication use in a large prospective cohort of patients with ankylosing spondylitis (AS) in daily clinical practice. Methods: Consecutive AS patients from the Groningen Leeuwarden AS (GLAS) cohort with baseline and 2‐year lateral radiographs of the thoracic and lumbar spine were included. Radiographs were scored for vertebral fractures by 2 readers according to the method of Genant et al. Differences in baseline characteristics between patients with and without radiographic vertebral fractures were explored. Results: Of 292 included AS patients, 59 (20%) had radiographic vertebral fractures at baseline, 15 (6%) developed new fractures, and 7 (2%) showed an increase in the severity of existing fractures during 2 years of follow‐up. Most fractures were mild and located in the midthoracic and thoracolumbar region of the spine. The presence of vertebral fractures was significantly associated with older age, higher body mass index, longer smoking duration, larger occiput‐to‐wall distance, more spinal radiographic damage, and lower hip bone mineral density (BMD). The development of new or progressive vertebral fractures was also associated with older age and low BMD. Patients using nonsteroidal antiinflammatory drugs (NSAIDs) at baseline showed less prevalent and incident vertebral fractures. Conclusion: In this large AS cohort in daily clinical practice, radiographic vertebral fractures were frequently present in AS, especially in older patients with more advanced disease, low hip BMD, and a less healthy lifestyle. Interestingly, NSAID use was associated with a reduced vertebral fractures risk.